Thrombospondin-2 and extracellular matrix assembly - Calabro, Nicole E.; Kristofik, Nina J.; Kyriakides, Themis R. (Biochimica et biophysica acta, 2014)
Numerous proteins and small leucine-rich proteoglycans (SLRPs) make up the composition of the extracellular matrix (ECM). Assembly of individual fibrillar components in the ECM, such as collagen, elastin, and fibronectin, is understood at the molecular level. In contrast, the incorporation of non-fibrillar components and their functions in the ECM are not fully understood. This review will focus on the role of the matricellular protein thrombospondin (TSP) 2 in ECM assembly. Based on findings in TSP2-null mice and in vitro studies, we describe the participation of TSP2 in ECM assembly, cell–ECM interactions, and modulation of the levels of matrix metalloproteinases (MMPs). Evidence summarized in this review suggests that TSP2 can influence collagen fibrillogenesis without being an integral component of fibrils. Altered ECM assembly and excessive breakdown of ECM can have both positive and negative consequences including increased angiogenesis during tissue repair and compromised cardiac tissue integrity, respectively. Proper ECM assembly is critical for maintaining cell functions and providing structural support. Lack of TSP2 is associated with increased angiogenesis, in part, due to altered endothelial cell–ECM interactions. Therefore, minor changes in ECM composition can have profound effects on cell and tissue function. This article is part of a Special Issue entitled Matrix-mediated cell behaviour and properties. •TSP2 functions primarily as a modulator of cell–ECM interactions and can influence the assembly of ECM.•More importantly, TSP2-null ECM enhances angiogenic responses.•Therefore, strategies can be pursued to reduce TSP2 and generate novel ECM via decellularization techniques.